Sword of kings [compact disc, unabridged] - Cornwell, Bernard (Cornwell, Bernard. Last kingdom., 2019)
It is a time of political turmoil once more as the fading King Edward begins to lose control over his successors and their supporters. There are two potential heirs, possibly more, and doubt over whether the once separate states of Wessex and Mercia will hold together. Despite attempts at pulling him into the political fray, Uhtred of Bebbanburg cares solely about his beloved Northumbria and its continuing independence from southern control. But an oath is a strong, almost sacred commitment and such a promise had been exchanged between Uhtred and Aethelstan, his onetime companion in arms and now a potential king.